Supporting e-science: the role of digital repositories in scientific communication - Vrana, Radovan (Array, 2010)
Digital technology has transformed scientific research and scientific communication profoundly. Scientists around the world use digital information resources such as digital repositories for their research and publishing of results of that research. Digital repositories are digital archives of intellectual output of university. They are also building blocks of e-science - data driven, data intensive and networked science. As their number increases, they are being analyzed for their good and weak sides in order to integrate them more firmly into our daily scientific practice.